Evaluation of The Drug-Free Village Program (Program Desa Bersinar) In Indonesia - Nataludin, Christian; Samputra, Palupi Lindasari (UI Scholars Hub, 2023)
The Government of Indonesia, has established the Drug-Free Village Program (Program Desa Bersih Narkoba – Desa Bersinar) to overcome the problem of drug abuse and illicit trade at the village level. This research aims to assess the effectiveness of the program implementation and map its constraints nationally. It uses descriptive quantitative methods on formal evaluation approaches and constraint mapping methods. We survey BNNP / BNNK's Prevention and Community Empowerment sub-coordinators throughout Indonesia, with 108 participants participating. Using the effectiveness evaluation criteria, based on the success indicators, according to the Desa Bersinar program implementation technical guidelines. The result shows that two factors explain the success of the Desa Bersinar program with an Eigenvalue of 64,118%. This means that the performance of Desa Bersinar can be explained by these two factors with an explanatory ability of 64.118%, while the rest is explained by other factors that have not been identified. Nationally, the Desa Bersinar program implementation has been effective, with index at 61.99%.